Manajemen Pendidikan Teknologi Kejuruan dan Vokasi - Hadrian, Balqis; Siti, Yuni; Effendi, Muhammad; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Teaching and Vocational Technology Education Management